Dropwise condensation of steam on ion implanted titanium surfaces - Rausch, Michael Heinrich; Leipertz, Alfred; Fröba, Andreas Paul (International Journal of Heat and Mass Transfer, 2010)
Stable dropwise condensation of steam was achieved by ion beam implantation of N(+) on titanium surfaces stabilized by a preoxidation procedure. It is pointed out that dropwise condensation can be adjusted by ion implantation in spite of increased wettability indicated by contact angle and surface free energy measurements. Our results suggest a nucleation mechanism possibly caused by interactions of nano-scale surface roughness and surface chemistry effects connected with precipitation of nitrides. Measured heat transfer coefficients for dropwise condensation were up to 5.5 times larger than values calculated by Nusselt film theory. No significant influence of the applied ion implantation parameters was found. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Dropwise condensation; Titanium; Ion implantation; Surface free energy; Nucleation; Heat transfer coefficient